Source of previous anti-TB treatment for re-treatment TB cases registered under Revised National Tuberculosis Control Program in Pondicherry - Niranjjan, R.; Sahu, Swaroop Kumar; Roy, Gautam; Vijaya Vani, S. Arul (International Journal Of Community Medicine And Public Health, 2017)
Background: Re-treatment TB cases are still a big challenge to National TB control programme. The objectives of the study were among retreatment TB cases, to study the source of previous anti-TB treatment, to find the time delays in initiating re-treatment and to find the risk factors for initiating retreatment under Revised National Tuberculosis Control Program (RNTCP) in Pondicherry. Methods: It was a cross sectional study. Source, date of completion or interruption of recent previous anti-TB treatment, missed doses, DM status; smoking and alcohol intake in the past TB treatment were collected using pretested structured questionnaire and available records. Data was entered in EpiData software version 3.1 and analysed using SPSS v20. Results: Of 241 re-treatment TB patients, the proportion of relapse, TAD, failure and others were 52%, 24%, 12.4% and 11.6 respectively. About 90% [95% CI (85.6-93.2)] had received their recent previous anti-TB treatment from RNTCP sources. In multivariate analysis, Age >24 years, below secondary level of education and relapse cases have independently associated with RNTCP source of previous TB treatment. The median time interval of re-registration for relapse, TAD, failure and others were 334, 211, 140 and 53 days respectively. This difference between groups are statistically significant (p<0.0001). Almost one out of four retreatment TB patient was known diabetic. More than half of retreatment TB patients had consumed alcohol during their recent previous TB treatment. Conclusions: The public-private partnership is better in Pondicherry as only 10% of re-treatment TB cases were previously treated from Non-RNTCP sources. There is a scope for reducing the time between declaration of failure and initiation of re-treatment TB regimen. Screening and appropriate counselling of all registered TB patients for smoking and alcohol intake may be necessary.